A vocational education and training subject teacher for fostering students' entrepreneurial skills—The development of a conceptual model - Kolho, Piia (International journal of training and development, 2024)
In the future, a significant portion of the workforce is expected to engage in self‐employment or pursue part‐time entrepreneurial endeavours, especially in vocational education and training (VET) fields where entrepreneurship serves as a predominant avenue of employment. The primary goal of this article is to investigate the interconnectedness of a teacher's autonomy, agency, and guiding behaviour and to understand their relevance to the teacher's pedagogical decisions and ability to effectively guide students toward entrepreneurship. To achieve this objective, semistructured interviews were conducted with eight VET subject teachers, employing predetermined concept definitions derived from prior research. Analysis of the interviews revealed a connection between these concepts, highlighting their influence on the pedagogical decisions made by VET teachers. However, minor variations were observed across diverse fields of VET. The study underscores the significance of autonomy, decision‐making capabilities and teacher agency in fostering students' entrepreneurial skills. It emphasises that autonomy alone is insufficient, and various factors either facilitate or hinder the promotion of entrepreneurship. This article contributes to entrepreneurship education research in two ways. First, it provides new information about the VET subject teacher as a promoter of students' entrepreneurial skills. Second, by presenting a theoretical model that helps to understand the factors influencing teachers' actions. The model, being novel, can be utilised to understand how VET teachers utilise autonomy and express agency in their work. Additionally, the research results are considered from an international perspective. The discourse revolves around the conceptual model, by exploring the reasons behind it, and considering subject teachers' professional identity as entrepreneurship teachers.